Risk assessment on geodiversity sites - Kubalíková, Lucie; Nováková, Eva; Kuda, František; Kirchner, Karel; Bajer, Aleš; Balková, Marie (Mendelova univerzita v Brně, 2023)
Geoconservation is an action of conserving and enhancing geological, geomorphological, hydrological and soil features and processes. Particular geoconservation measures are very often applied on the site-level to protect important geodiversity sites. Nevertheless, despite established legal protection and related geoconservation activities, threats to geodiversity sites related to the multiple use and human society demands can arise and reaching a compromise can be difficult. In this contribution, a two-level threat assessment is applied and discussed. The first level of threat assessment is based on the already used criteria within geosite/geomorphosite concept. The second level of threat assessment is represented by Risk Assessment Matrix, which may be considered a useful tool providing a complex view on the threats to geodiversity sites. The methods are applied on two different sites and their advantages and limits are discussed. Based on the assessment, specific management proposals may be implemented in order to balance conservation needs and demands resulting from human activities related to the sites.
Keywords: geoconservation; risk assessment matrix; degradation risk; geosites; geomorphosites